PENDAMPINGAN PENGURUSAN IZIN PIRT UMKM JAMU WR9 DI DESA WRINGINSONGO KECAMATAN TUMPANG KABUPATEN MALANG : - - Hudriyah Mundzir; Khrisna Hadiwinata; Shohib Muslim; Muhammad Akhlis Rizza; Mohammad Abdullah Anshori; Muhammad Nanak Zakaria (P3M Politeknik Negeri Malang, 2024)
Community service activities were carried out in Tumpang District, Malang Regency with partners, namely UMKM Jamu WR9 which is a representative of MSMEs in Wringinsongo Village, Tumpang District, Malang Regency. These business actors include the production and sales processes. Community service activities are carried out with the aim of providing understanding to business actors regarding the factors supporting business activities, namely legality and business management factors, in this case PIRT licensing so that business activities carried out are not only profit-oriented, but business activities can continue to develop in the future. by paying attention to and implementing supporting factors for business activities and by providing assistance with PIRT licensing. The activity implementation method consists of three stages. The first preparation stage includes pre-survey, team formation, proposal creation and submission, team and partner coordination as well as preparation of tools and materials to assist PIRT licensing. The second stage is the program implementation stage in the form of assistance which begins with discussion and preparation for PIRT management by providing a sealer machine and stove. The third stage is the evaluation and reporting stage. Evaluation is carried out by comparing the conditions of partners before and after program implementation using interview and observation methods. After that, a report is prepared for subsequent publication. With the implementation of this program, there will be an improvement in society's value order in the field of education, especially in the fields of economics and law. Keywords: PIRT permit, UMKM